Physiologically based pharmacokinetic modeling of caffeine in patients with liver cirrhosis: Implications for exposure-guided dose adjustment - Se-In Lee; Chi-Ho Lee; Ji-Hun Jang; Seung-Hyun Jeong (Environmental Toxicology and Pharmacology, 2026)

Dielectric oligonucleotide fragments enable ultralow threshold photomultiplication in infrared quantum dot photodetectors - Yongnam Ahn; Jinwoo Shin; Woo Hyuk Jung; Yong Ho Cho; Minjung Yang; In-Suh Lee; Jaewoo Jeong; Taeho Han; Seoryeon Jeong; Jin Ah Lee; Chae Hyeong Ha; Yoon Jang Chung; et al. (Chemical Engineering Journal, 2026)

Quantifying the joint effects of soil salinity and fertility on rice growth and yield variability in coastal paddies of southwestern Korea - Seo-Woo Park; Nuri Baek; Se-In Lee; Eun-Seo Shin; Hyun-Jin Park; Han-Yong Kim; Kyo-Suk Lee; Kwang-Seung Lee; Nurgul Kitir Sen; Woo-Jung Choi (Journal of Soils and Sediments, 2026)

Estimation of soil moisture retention using pedo-transfer functions based on soil particle-size distribution and organic matter of Korean soils - Se-In Lee; Seung-Oh Hur (Paddy and Water Environment, 2026)
Soil moisture retention is one of the most important soil physical properties for hydrological analysis and for determining irrigation water requirements for agricultural crops. However, because measuring soil moisture retention at multiple matric potentials is time consuming and labor-intensive and pedo-transfer functions (PTFs) based on soil properties is widely used, soil moisture retention is estimated indirectly. Although PTFs are influenced by various soil characteristics and exhibit considerable variability, this variability has rarely been investigated, particularly for Korean soils. This study was aimed to develop and evaluate the new-PTFs at 10, 33, and 1500 kPa of soil moisture retention (θ 10 , θ 33, and θ 1500 ) for Korean soil using multiple linear regression model for soil samples ( n = 1,302 and 138 for developing and evaluating, respectively) across Korea. The estimated soil moisture retentions values showed positive correlations with the measured values of soil moisture retention of new-PTFs ( R 2 = 0.78, 0.78, and 0.65 for θ 10 , θ 33, and θ 1500 , respectively) compared to previously established model. The RMSE and MAE values for the new PTFsranged from 4.83 to 6.16 and from 3.37 to 4.86, respectively, by showing the lowest values compared to other models. The values of NSE were above 0.5 for all, except for θ 1500 (NSE = 0.21), indicating generally accepted model performance between estimated and measured values. The developed new-PTFs at θ 10 , θ 33, and θ 1500 offer improved prediction of soil water retention for Korean soils than previously established models, providing a valuable tool for soil water management and agricultural applications.

Substitution of lithogenic with pedogenic soil carbonates in Korean coastal rice paddy under desalinization: Evidences from δ13C - Seo-Woo Park; Nuri Baek; Eun-Seo Shin; Bo-Seong Seo; Se-In Lee; Kwang-Seung Lee; Seok-In Yun; Hyun-Jin Park; Sang-Mo Lee; Woo-Jung Choi (Agriculture, Ecosystems & Environment, 2026)

Multiple measures to mitigate methane emissions from organic rice fields: a review and future challenges - Nuri Baek; Se-In Lee; Husna Israt Pia; Seo-Woo Park; Eun-Seo Shin; Miwa M. Yashima; Han-Yong Kim; Hyun-Jin Park; Woo-Jung Choi (Journal of Soils and Sediments, 2025)

In vitro study of silver nanoparticles-induced embryotoxicity using a rat whole embryo culture model - Woong-Il Kim; So-Won Pak; Se-Jin Lee; Sin-Hyang Park; In-Sik Shin; Changjong Moon; Wook-Jun Yu; Sung-Hwan Kim; Jong-Choon Kim (Toxicological Research, 2025)

Estimation of the electrical conductivity of saturated paste from soil–water extracts of coastal saline paddy soils using random forest and multiple regression models - Hyun-Jin Park; Nuri Baek; Bo-Seong Seo; Young-Jae Jeong; Hye In Yang; Se-In Lee; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Journal of Soils and Sediments, 2024)

Particulate matter-mediated oxidative stress induces airway inflammation and pulmonary dysfunction through TXNIP/NF-κB and modulation of the SIRT1-mediated p53 and TGF-β/Smad3 pathways in mice - Ji-Hye Ha; Ba-Wool Lee; Da-Hye Yi; Se-Jin Lee; Woong-Il Kim; So-Won Pak; Hyeon-Young Kim; Sung-Hwan Kim; In-Sik Shin; Jong-Choon Kim; In-Chul Lee (Food and Chemical Toxicology, 2024)

Multilayer composite membranes composed of carbon molecular sieve membranes sandwiched between stacked zeolite nanosheets - Dong Yun Han; Ah Hyun Lee; Su Kyung Kang; Se Wan Kim; Woo Chul Kwak; In-Seok Jeon; Seunghwa Yang; Pyung Soo Lee (Chemical Engineering Journal, 2024)

Diesel particulate matter aggravates cyclophosphamide-induced testicular toxicity in mice via elevating oxidative damage - Woong-Il Kim; Je-Oh Lim; So-Won Pak; Se-Jin Lee; Yea-Gin Yang; In-Sik Shin; Changjong Moon; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2024)

Improving spray performance of vehicle disinfection systems in livestock farms using computational fluid dynamics analysis - Lak-yeong Choi; Se-yeon Lee; Jinseon Park; Se-woon Hong; Kehinde Favour Daniel; Hyo-hyeog Jeong; In-bok Lee (Computers and Electronics in Agriculture, 2023)

Cold-induced adaptive thermogenesis is impaired by exposure of Asian sand dust in mice - Bernadette B. Bagon; Junhyeong Lee; Merc Emil Matienzo; Se-Jin Lee; So-Won Pak; Keon Kim; Jeongmin Lee; Chang-Min Lee; In-Sik Shin; Changjong Moon; Min-Jung Park; Dong-il Kim (Journal of Thermal Biology, 2023)

Effects of melamine and cyanuric acid on placental and fetal development in rats - Woong-Il Kim; So-Won Pak; Se-Jin Lee; Changjong Moon; In-Sik Shin; In-Chul Lee; Jong-Choon Kim (Food and Chemical Toxicology, 2023)

Development and validation of an air recirculated ventilation system, Part 1: Application of system in a pig farm and evaluation of pig productivity during winter - Jun-gyu Kim; In-bok Lee; Andre Aarnink; Bong-joo Lee; Deuk-young Jeong; Hyo-hyeog Jeong; Se-han Kim; Bong-kuk Lee; Dong-kyu Lee (Biosystems Engineering, 2023)

Development and validation of an air recirculated ventilation system, Part 2: Evaluation of pig productivity in spring and summer seasons including examination of cooling methods - Jun-gyu Kim; In-bok Lee; Deuk-young Jeong; Se-jun Park; Jeong-hwa Cho; Rack-woo Kim (Biosystems Engineering, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Influence of ultrafast microwave deposition on morphology and growth mechanism of WO3 nanosheet photoanode for efficient bacterial inactivation and decomposition of organic pollutants - In-Seon Hwang; Mahadeo A. Mahadik; Min Seok Song; Se-Won Lee; Byung-Taek Oh; Hyun Hwi Lee; Weon-Sik Chae; Sun Hee Choi; Jum Suk Jang (Journal of Environmental Chemical Engineering, 2023)

Correction: Antioxidant activity of edible sprouts and phytosterol contents by HPLC/UV analysis - Juree Kim; Ji Hyun Kim; Se In Bang; Hanna Shin; Eun Ju Cho; Sanghyun Lee (Horticulture, Environment, and Biotechnology, 2023)

Determination of the optimal location and the number of sensors for efficient heating, ventilation, and air conditioning system operation in a mechanically ventilated pig house - Uk-Hyeon Yeo; Sang-Yeon Lee; Se-Jun Park; Jun-Gyu Kim; Deuk-Young Jeong; Cristina S. Decano-Valentin; Rack-Woo Kim; In-Bok Lee (Biosystems Engineering, 2023)

Modeling for the estimating the adsorption property of fruit waste-based biosorbents for the removal of organic micropollutants - Bo-Gyeon Cho; Jae-Ho Lee; Hye-In Kim; Se-Been Mun; Se-Ra Jin; Dae Geun Kim; Chul-Woong Cho; Yeoung-Sang Yun (Environmental Research, 2023)

Toll-like receptor 4 is a key regulator of asthma exacerbation caused by aluminum oxide nanoparticles via regulation of NF-κB phosphorylation - Je-Oh Lim; Woong-Il Kim; So-Won Pak; Se-Jin Lee; Sung-Hyeuk Park; In-Sik Shin; Jong-Choon Kim (Journal of Hazardous Materials, 2023)

Estimation of ventilation rate in a piglet house considering ventilation system characteristics - Young-bae Choi; Jun-gyu Kim; Jeong-hwa Cho; Sang-yeon Lee; Se-jun Park; Cristina Decano-Valentin; Deuk-young Jeong; In-bok Lee (Biosystems Engineering, 2023)

Exposure to China dust exacerbates testicular toxicity induced by cyclophosphamide in mice - Woong-Il Kim; Je-Oh Lim; So-Won Pak; Se-Jin Lee; In-Sik Shin; Changjong Moon; Jeong-Doo Heo; Jong-Choon Kim (Toxicological Research, 2023)

Evaluation of genotoxicity of SUNACTIVE Zn-P240 in vitro and in vivo - Jeong-Hyun Lim; Jong-Yun Lee; Woong-Il Kim; So-Won Pak; Se-Jin Lee; In-Sik Shin; Jong-Choon Kim (Toxicological Research, 2022)

Antioxidant activity of edible sprouts and phytosterol contents by HPLC/UV analysis - Juree Kim; Ji Hyun Kim; Se In Bang; Hanna Shin; Eun Ju Cho; Sanghyun Lee (Horticulture, Environment, and Biotechnology, 2022)
This study evaluated the in vitro radical scavenging activities of edible tree sprouts, particularly those of the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH), hydroxyl radical, and singlet oxide radical, to assess their antioxidant activities. Additionally, stigmasterol (ST) and β-sitosterol (BS) were analyzed using HPLC/UV. The edible sprouts of Eleutherococcus senticosus (ESC) and Morus alba (MAB) exhibited the highest DPPH scavenging activity among other edible sprouts. A reverse-phase column was used in an isocratic elution system, after which UV detection was performed at 210 nm. ST and BS analyses indicated that ESC sprouts contained the highest amounts of ST (9.99 mg·g − 1 extract), whereas MAB sprouts contained the highest concentrations of BS (14.69 mg·g − 1 extract). In conclusion, the highest antioxidant activity was observed in the edible sprouts with the highest phytosterol content. Therefore, our findings provide a theoretical basis for the development of plant-based functional foods or supplements with antioxidant properties.

Subchronic Toxicity Evaluation of Aluminum Oxide Nanoparticles in Rats Following 28-Day Repeated Oral Administration - Sung-Hyeuk Park; Je-Oh Lim; Woong-Il Kim; So-Won Park; Se-Jin Lee; In-Sik Shin; Changjong Moon; Je-Hein Kim; Jeong-Doo Heo; Jong-Choon Kim (Biological Trace Element Research, 2022)

Land-use type, and land management and disturbance affect soil δ15N: a review - Woo-Jung Choi; Jin-Hyeob Kwak; Hyun-Jin Park; Hye In Yang; Se-In Park; Zhihong Xu; Sang-Mo Lee; Sang-Sun Lim; Scott X. Chang (Journal of Soils and Sediments, 2020)

In Situ Gelling Hydrogel with Anti-Bacterial Activity and Bone Healing Property for Treatment of Osteomyelitis - Sun Woo Jung; Se Heang Oh; In Soo Lee; June-Ho Byun; Jin Ho Lee (Tissue Engineering and Regenerative Medicine, 2019)

Sorption of Pb in chemical and particle-size fractions of soils with different physico-chemical properties - Hyun-Jung Park; Hyun-Jin Park; Hye In Yang; Se-In Park; Sang-Sun Lim; Jin-Hyeob Kwak; Goon-Taek Lee; Sang-Mo Lee; Man Park; Woo-Jung Choi (Journal of Soils and Sediments, 2019)

Simultaneous analysis and exposure assessment of migrated bisphenol analogues, phenol, and p-tert -butylphenol from food contact materials - Joungboon Hwang; In-Ae Bae; Chanyong Lee; Subi Lee; Jae Chun Choi; Se-Jong Park; Jin-Hwan Hong; Gaeho Lee; MeeKyung Kim (Food Additives & Contaminants: Part A, 2018)

Improved dissipation kinetic model to estimate permissible pre-harvest residue levels of pesticides in apples - Jeong-In Hwang; Hyo-Young Kim; Sang-Hyeob Lee; Se-Yeon Kwak; Andrew R. Zimmerman; Jang-Eok Kim (Environmental Monitoring and Assessment, 2018)

Optimization of TILLING system based on capillary electrophoresis for targeted selection of pepper gene mutants - Han Sol Kang; Sang Hoon Kim; Sang Woo Lee; Se Won Kim; Jaihyunk Ryu; Jin-Baek Kim; Seon-In Yeom; Si-Yong Kang; Yeong Deuk Jo (Horticulture, Environment, and Biotechnology, 2018)

Evaluating laboratory-based classification potentials of heavy metal contaminated soils using spectro-radiometer and hyper-spectral imagery - SeongJoo Kang; Keum-Young Lee; Eui-Ik Jeon; Se-Jong Yu; In Hwan Shin; Oh-Seob Kwon (Spatial Information Research, 2018)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Genetic analysis of COL11A2 in Korean patients with autosomal dominant non-syndromic hearing loss - Sang-Joo Kim; Hong-Joon Park; Borum Sagong; Seung-Hyun Bae; Se-Kyung Oh; Jeong-In Baek; Jae Young Choi; Kyu-Yup Lee; Un-Kyung Kim (Genes & Genomics, 2016)

Genetic characteristics of highly pathogenic H5N8 avian influenza viruses isolated from migratory wild birds in South Korea during 2014-2015 - Young-Jae Si; Won Suk Choi; Young-Il Kim; In-Won Lee; Hyeok-Il Kwon; Su-Jin Park; Eun-Ha Kim; Se mi Kim; Jin-Jung Kwon; Min-Suk Song; Chul-Joong Kim; Young-Ki Choi (Archives of Virology, 2016)

No association of CLOCK 3111T/C polymorphism with diurnal preference and sleep quality in Korean adults - Seong Jae Kim; Jung Hie Lee; Se Yong Lee; Jun-Won Hwang; In Bum Suh (Sleep and Biological Rhythms, 2016)

Bladder reconstruction using stem cells seeded on multilayered scaffolds in a mucosa preserving partial cystectomy model - Kshitiz Raj Shrestha; Yong Hyun Park; Yong Sun Choi; In Gul Kim; Shuyu Piao; Ae Ryang Jung; Seung Hwan Jeon; Se Heang Oh; Jin Ho Lee; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2015)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

Apoptosis imaging studies in various animal models using radio-iodinated peptide - Wonjung Kwak; Yeong Su Ha; Nisarg Soni; Woonghee Lee; Se-Il Park; Heesu Ahn; Gwang Il An; In-San Kim; Byung-Heon Lee; Jeongsoo Yoo (Apoptosis, 2015)

A promoter polymorphism of MSTN g.−371T>A and its associations with carcass traits in Korean cattle - Sang-Hyun Han; In-Cheol Cho; Moon-Suck Ko; Eun-Young Kim; Se-Pill Park; Sung-Soo Lee; Hong-Shik Oh (Molecular Biology Reports, 2012)

Complete nucleotide sequence analysis of a Korean strain of hepatopancreatic parvovirus (HPV) from Fenneropenaeus chinensis - Subbiah Jeeva; Se-Won Kang; Yong-Seok Lee; In Kwon Jang; Hyung Chel Seo; Tae-Jin Choi (Virus Genes, 2012)

Comparative analysis of expressed sequence tags (ESTs) between normal group and softness syndrome group in Halocynthia roretzi - Ji Eun Jeong; Se Won Kang; Yun Kyung Shin; Je Cheon Jun; Young-Ok Kim; Young Baek Hur; Jae-Hyung Kim; Sung-Hwa Chae; Jun-Sang Lee; In ho Choi; Yeon Soo Han; Dae-Hyun Seog; et al. (Molecular & Cellular Toxicology, 2011)

Developmental expression of plasma glutathione peroxidase during mouse organogenesis - Ki Youn Jung; In-Jeoung Baek; Jung-Min Yon; Se-Ra Lee; Mi-Ra Kim; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2011)

Phospholipid hydroperoxide glutathione peroxidase gene is regulated via an estrogen and estrogen receptor signaling in cultured mouse fetuses - In-Jeoung Baek; Ki Youn Jung; Jung-Min Yon; Se-Ra Lee; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (In Vitro Cellular & Developmental Biology - Animal, 2011)

Identification of an OsPR10a promoter region responsive to salicylic acid - Seon-Hee Hwang; In Ah Lee; Se Won Yie; Duk-Ju Hwang (Planta, 2008)
Orysa sativa pathogenesis-related protein 10a ( Os PR10a) was induced by pathogens, salicylic acid (SA), jasmonic acid (JA), ethephon, abscisic acid (ABA), and NaCl. We tried to analyze the OsPR10a promoter to investigate the transcriptional regulation of OsPR10a by SA. We demonstrated the inducibility of OsPR10a promoter by SA using transgenic Arabidopsis carrying Os PR10a:GFP as well as by transient expression assays in rice. To further identify the promoter region responsible for its induction by SA, four different deletions of the OsPR10a promoter were made, and their activities were measured by transient assays. The construct containing 687-bp OsPR10a promoter from its start codon exhibited a six-fold increase of induction compared to the control in response to SA. Mutation in the W-box like element 1 (WLE 1) between 687 and 637-bp from TGACA to TGAAA completely abolished induction of the OsPR10a promoter by SA, indicating that the WLE 1 between −687 and −637 of OsPR10a promoter is important in SA-mediated OsPR10a expression. We show for the first time that the W-box like element plays a role in SA mediated PR gene expression.

The spatio-temporal expression pattern of cytoplasmic Cu/Zn superoxide dismutase (SOD1) mRNA during mouse embryogenesis - Jung-Min Yon; In-Jeoung Baek; Se-Ra Lee; Yan Jin; Mi-Ra Kim; Sang-Seop Nahm; Jong-Soo Kim; Byeongwoo Ahn; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2008)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Tissue expression and cellular localization of phospholipid hydroperoxide glutathione peroxidase (PHGPx) mRNA in male mice - In-Jeoung Baek; Dong-Suk Seo; Jung-Min Yon; Se-Ra Lee; Yan Jin; Sang Soep Nahm; Jae-Hwang Jeong; Young-Kug Choo; Jong-Koo Kang; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2007)